Differential intracellular fate of Burkholderia pseudomallei 844 and Burkholderia thailandensis UE5 in human monocyte-derived dendritic cells and macrophages - Jaruek Charoensap (2018)
Background: Burkholderia pseudomallei (Bp) is a category B biothreat organism that causes a potentially fatal disease in humans and animals, namely melioidosis. Burkholderia thailandensis (Bt) is another naturally occurring species that is very closely related to Bp. However, despite this closely related genotype, Bt is considered avirulent as it does not cause the disease. In the present study, we compared the growth kinetics of B. pseudomallei strain 844 (Bp-844) in human monocyte-derived dendritic cells (MoDCs) and macrophages (Mφs), as well as its ability to stimulate host cell responses with those of B. thailandensis strain UE5 (Bt-UE5). Results: Primary human MoDCs and Mφs were infected with Bp-844 and its intracellular growth kinetics and ability to induce host cell responses were evaluated. The results were compared with those obtained using the Bt-UE5. In human MoDCs, both bacteria were similar in respect to their ability to survive and replicate intracellularly, induce upregulation of costimulatory molecules and cytokines and bias T helper cell differentiation toward a Th1 phenotype. By contrast, the two bacteria exhibited different growth kinetics in human Mφs, where the intracellular growth of Bt-UE5, but not Bp-844, was significantly suppressed. Moreover, the ability of Mφs to kill Bp-844 was markedly enhanced following stimulation with IFN-γ. Conclusion: The data presented showed that while both strains were similar in their ability to survive and replicate in human MoDCs, only Bp-844 could readily replicate in human Mφs. Both bacteria induced similar host cellular responses, particularly with regard to their ability to bias T cell differentiation toward a Th1 phenotype. © 2009 Charoensap et al; licensee BioMed Central Ltd.